Management Quality Control in Islamic Education - Rangga Sa'adillah S.A.P.; Daiyatul Husna; Dewi Winarti (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat Lamongan, 2021)
This article aims to examine and elaborate on the terms of quality control management from the perspective of Islamic education. Quality control is important in the world of education because quality control is related to the consistency of Islamic education institutions in ensuring that the quality of these educational institutions is feasible to operate and compete in the national and international education arena. To control the quality of education, this article offers two models, namely total quality management and excellent service-based quality control management. The thing that must be considered in quality control management is not only to pay attention to three aspects of quality control, namely input, process, and output. More than that, in carrying out quality control management, you must also provide excellent service that really shows partiality to the customer.